Analysis of the Influence of Service Orientation on Job Satisfaction and Organizational Commitment in the Hospitality Industry (Case Study: Three Star Hotels in Depok City) - Iqbal Banyu Sunarya (International Journal Labs, 2026)
The rapid growth of the tourism sector in Indonesia has increased the demand for high-quality services in the hospitality industry, making human resource management a critical factor in achieving organizational sustainability. This research aims to analyze the influence of service orientation on job satisfaction and employee organizational commitment in the hospitality industry, with a case study of three-star hotels in Depok City, namely Hotel Santika, Hotel Bumi Wiyata, and The Margo Hotel. This study uses a quantitative approach with a survey method involving 99 employees. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM) with SmartPLS. The results of the study show that service orientation has a positive and significant effect on employee job satisfaction. Service orientation also has a positive effect on organizational commitment, albeit with a relatively smaller level of influence. In addition, job satisfaction has been proven to have a very strong positive influence on organizational commitment. These findings confirm that improving service orientation and employee job satisfaction is an important factor in strengthening organizational commitment and supporting the sustainability of the hospitality industry.